Methodology and guidelines for geovisualizing archaeological excavation data: the case of Sikyon, Greece - Mousouris , Spiridon; Lolos , Yannis; Giannakoula , Christina (Journal of Greek Archaeology, 2024)
To the best of our knowledge, most platforms or apps that geovisualize archaeological excavations are limited to displaying the excavated areas and providing a brief description and interpretation of the remains. Even though the validity of this information is not in question, there are usually no details available to the end user nor is the information in any way connected to the relevant excavation data. As Huvila and Huggett point out, the limiting factor in such cases is the insufficient understanding of the archaeological remains and the poor level of documentation. As a result, the end user is effectively a passive recipient of a digested knowledge without being able to access the source of that knowledge.